Optical IP network system using 16 wavelengths of Coarse WDM technologies and Layer-3 switch - Nguyen, Viet Hoang; Marsden, Adelys; Fujimoto, Satoru; Katsuyama, Yutaka (Photonics Letters of Poland, 2013)
We have proposed and experimentally demonstrated an optical network system using 16 wavelengths of Coarse Wavelength-Division-Multiplexing (CWDM) technology and Layer-3 Switch. For keeping the speed of 1000Mbps at the bus IFs, CWDM technology is employed, and 16 wavelengths are allocated to 16 bus IF, respectively. The system consists of a gateway which contains a controller and a server to connect terminals and public providers. The optical IP networks can be scalable by adjusting the number of wavelengths and optical transceiver. We believe this novel scheme is a practical scheme to be applied for future broadband networks. Full Text: PDF References Adel A. M. Saleh and Jane M. Simmons, "Architectural principles of optical regional and metropolitan access networks", J. Lightwave Tech., vol.17, pp.2431-2448, 1999. CrossRef Jeremy De Clercq and Olivier Paridaens, "Scalability implications of virtual private networks", IEEE Comm. Magazines, vol.40, pp.151-157, 2002. CrossRef A. Jourdan, D. Chiaroni, and E. Dotaro, "The perspective of optical packet switching in IP dominant backbone and metropolitan networks ", IEEE Comm. Magazines, vol.39, pp.136-141, 2001. CrossRef B.St Arnaud, Jing Wu and B.Kalali, "Customer-controlled and -managed optical networks", J. Lightwave Tech., vol. 21, pp. 2804-2810, Nov 2003. CrossRef M Hashimoto, A Ueno, M Taniue, S Kawase, O Koyama and Y Katsuyama, "Design and Control System for Regional CWDM Optical IP Networks with Reconfigurable Optical Add/Drop Multiplexers ", The 9th International Conference on Telecommunications, Zagreb, Croatia, 23-30, June 2007. CrossRef M. Hashimoto, A. Ueno, M. Taniue, S. Kawase, O. Koyama, and Y. Katsuyama, International Journal of Innovative Computing, Information and Control, 4, No.6, pp. 1299-1313, 2008. DirectLink M. Hashimoto, O. Koyama, M.D. Nooruzzaman, and Y. Katsuyama, "Bi-directional lightpath reconfiguration in regional IP-over-WDM networks by a centralized control system", IEEJ Trans. Electrical and Electronic Engineering, vol.4, no.3 pp.425-434, 2009 CrossRef M.D. Nooruzzaman, Y. Harada, O. Koyama, and Y. Katsuyama, "Proposal of Stackable ROADM for Wavelength Transparent IP-over-CWDM Networks", IEICE Trans. Commun., vol.E91-B, no.10, pp.3330-3333, Oct. 2008. CrossRef S. Fujimoto, K. Tsujimura, S. Hayashi, J. Wang and Y. Katsuyama, in Proc. of 7th APCC, pp.9-12, Tokyo, Sept., 2001.